Evaluation of Antioxidant Activity, Total Flavonoids, Tannins and Phenolic Compounds in Psychotria Leaf Extracts - Anelise Samara Nazari Formagio; Carla Roberta Ferreira Volobuff; Matheus Santiago; Claudia Andrea Lima Cardoso; Maria do Carmo Vieira; Zefa Valdevina Pereira (MDPI AG, 2014)
The antioxidant activity of Psychotria carthagenensis, P. leiocarpa, P. capillacea and P. deflexa (Rubiaceae) extracts were investigated, and the concentrations of total phenolics, flavonoids, condensed tannins and flavonols were determined. The chemical compositions of the extracts were investigated using the high performance liquid chromatography (HPLC/PAD) method. We used 1,1-diphenyl-1-picrylhydrazyl free radical (DPPH), β-Carotene bleaching and 2,2-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cations to determine antioxidant activity. The ability to scavenge radical was measured in these experiments by the discoloration of the solution. Concentrations of constituents were measured spectrophotometrically. P. carthagenensis and P. capillacea exhibited the highest antioxidant activity, in the DPPH test, β-carotene bleaching and ABTS system. The highest phenolic, flavonoid, condensed tannin and flavonol concentration was found in P. carthagenensis and P. capillacea extracts. HPLC-PDA analysis of P. carthagenensis and P. capillacea revealed hydroxycinnamic acid (p-coumaric acid). This is the first report on the antioxidant properties and constituent analysis of these Psychotria extracts.